2009
DOI: 10.1002/syn.20657
|View full text |Cite
|
Sign up to set email alerts
|

Alteration of synaptic transmission in the hippocampal‐mPFC pathway during extinction trials of context‐dependent fear memory in juvenile rat stress models

Abstract: The medial prefrontal cortex (mPFC) has been proposed to be essential for extinction of fear memory, but its neural mechanism has been poorly understood. The present study examined whether synaptic transmission in the hippocampal-mPFC pathway is related to extinction of context-dependent fear memory in freely moving rats using electrophysiological approaches combined with behavioral analysis. Population spike amplitude in the mPFC was decreased during the first extinction trial by exposure to contextual fear c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
28
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
10

Relationship

4
6

Authors

Journals

citations
Cited by 41 publications
(29 citation statements)
references
References 37 publications
1
28
0
Order By: Relevance
“…We have also recently reported that pups exposed to footshock (FS) stress from postnatal days 21 to 25 (3wFS) have an altered anxiety-related behavior as adult rats (Konno et al 2007;Matsumoto et al 2008;Koseki et al 2009;Matsuzaki et al 2009). In these studies, the 3wFS increased the ratio of spent time in open arms in an elevated plus-maze test and reduced the number of 5-HT-like immunoreactive cells in the median raphe nucleus (MRN) compared with the non-FS control group.…”
Section: Introductionmentioning
confidence: 96%
“…We have also recently reported that pups exposed to footshock (FS) stress from postnatal days 21 to 25 (3wFS) have an altered anxiety-related behavior as adult rats (Konno et al 2007;Matsumoto et al 2008;Koseki et al 2009;Matsuzaki et al 2009). In these studies, the 3wFS increased the ratio of spent time in open arms in an elevated plus-maze test and reduced the number of 5-HT-like immunoreactive cells in the median raphe nucleus (MRN) compared with the non-FS control group.…”
Section: Introductionmentioning
confidence: 96%
“…Acute stress has been shown to inhibit LTP formation in the hippocampal-mPFC pathway (30). Furthermore, our previous study indicated that the PSA in this pathway was reduced during exposure to the fearconditioned stimulus and that this reduction was attenuated in parallel with the extinction of conditioned fear (31). Thus, we inferred that the hippocampal-mPFC pathway was important for the regulation of emotion, especially during fear extinction.…”
Section: Discussionmentioning
confidence: 75%
“…We did not use higher doses of tandospirone because a higher dose (10 mg/kg) dramatically increased omissions (> 50) in our preliminary study. The dose of tandospirone (1 mg/kg) was chosen based on our previous reports (22,23). This dose of tandospirone has consistently exerted anxiolytic actions in rats.…”
Section: Experiments 1: the Effects Of Tandospirone On Impulsive Actionmentioning
confidence: 99%